Industry perspectives on market access of innovative drugs - Kim ePauwels; Isabelle eHuys; Minne eCasteels; Steven eSimoens (Frontiers Media S.A., 2016)
This study presents industry perspectives on the challenges related to market access of innovative drugs in general and oncology drugs in specific. Fifteen interviews were conducted with representatives of pharmaceutical companies and industry associations. Interviewees call for a broader recognition of value within the assessment and appraisal of drugs. According to interviewees, focus on value is jeopardized by the lack of a common value definition across Europe, poor availability and validity of value measures and cost-saving measures such as external reference price setting and cost-effectiveness analysis at the side of the payers. Centralized assessment of relative-effectiveness at European level would provide a common value estimate across member states, independent of financial drivers. Empirical evidence on patient reported outcomes and societal preferences is however essential in the development of a value definition. Furthermore, value-based pricing would imply a dynamic approach where the price is differentiated across indications and across the lifecycle of the drug, especially in fields such as oncology. Financial drivers however also threat the application of value-based pricing at the side of the industry, making value-based profitability a more appropriate term.